Vaccination in immunocompromised host: Recommendations of Italian Primary Immunodeficiency Network Centers (IPINET). Issue 24 (7th June 2018) - Martire, Baldassarre; Azzari, Chiara; Badolato, Raffaele; Canessa, Clementina; Cirillo, Emilia; Gallo, Vera; Graziani, Simona; Lorenzini, Tiziana; Milito, Cinzia; Panza, Raffaella; Moschese, Viviana; ,
Abstract: Infectious complications are a major cause of morbidity and mortality in patients with primary or secondary immunodeficiency. Prevention of infectious diseases by vaccines is among the most effective healthcare measures mainly for these subjects. However immunocompromised people vary in their degree of immunosuppression and susceptibility to infection and, therefore, represent a heterogeneous population with regard to immunization. To date there is no well- established evidence for use of vaccines in immunodeficient patients, and indications are not clearly defined even in high-quality reviews and in most of the guidelines prepared to provide recommendations for the active vaccination of immunocompromised hosts. The aim of this document is to issue recommendations based on published literature and the collective experience of the Italian primary immunodeficiency centers, about how and when vaccines can be used in immunocompromised patients, in order to facilitate physician decisions and to ensure the best immune protection with the lowest risk to the health of the patient.